2021
DOI: 10.3390/biom12010036
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Polyunsaturated Fatty Acids in Endometrial Receptivity

Abstract: Endometrial receptivity plays a crucial role in fertilization as well as pregnancy outcome in patients faced with fertility challenges. The optimization of endometrial receptivity may help with normal implantation of the embryo, and endometrial receptivity may be affected by numerous factors. Recently, the role of lipids in pregnancy has been increasingly recognized. Fatty acids and their metabolites may be involved in all stages of pregnancy and play a role in supporting cell proliferation and development, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 181 publications
0
11
0
Order By: Relevance
“…53 Fatty acid metabolism is reported to regulate decidualization. 54 Two enzymes, ELOVL5 and ACAA2, which were identified as DEGs in our study, were involved in the enriched 'fatty acid elongation' pathway (Figures 3E and Tables S2 and S3). Upregulation of ELOVL5 may disturb the production of monounsaturated and polyunsaturated fatty acids of different chain lengths, which may cause decidualization dysfunction through lipid peroxidation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…53 Fatty acid metabolism is reported to regulate decidualization. 54 Two enzymes, ELOVL5 and ACAA2, which were identified as DEGs in our study, were involved in the enriched 'fatty acid elongation' pathway (Figures 3E and Tables S2 and S3). Upregulation of ELOVL5 may disturb the production of monounsaturated and polyunsaturated fatty acids of different chain lengths, which may cause decidualization dysfunction through lipid peroxidation.…”
Section: Discussionmentioning
confidence: 65%
“…Upregulation of ELOVL5 may disturb the production of monounsaturated and polyunsaturated fatty acids of different chain lengths, which may cause decidualization dysfunction through lipid peroxidation. 54 Downregulation of ACAA2 may reduce the breakdown of fatty acids into acetyl-CoA and energy, leading to impaired decidualization and embryo implantation. 55 Similarly, dysregulation of cholesterol metabolism might alter steroid hormone synthesis affecting the acceptance and maintenance of a competent blastocyst in the non-pregnant group.…”
Section: Discussionmentioning
confidence: 99%
“…In the CSD group, N-(3-hydroxy-eicosanoyl)-homoserine lactone and Ternatin were significantly increased, while various fatty acids were significantly decreased. Several of these fatty acids, which were decreased in the CSD group, were previously shown to have protective effects on the endometrium, including 12-Oxo-2,3-dinor-10,15-phytodienoic acid, and 3-Methylsuberic acid ( 22 ). N-(3-hydroxy-eicosanoyl)-homoserine lactone has been shown to promote apoptosis of various cells in vivo , including macrophages ( 23 ), vascular endothelial cells ( 24 ), and fibroblasts ( 25 ), through mitochondrial damage received by reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with PUFAs showed an association with clinical pregnancy and improved folliculogenesis, oocyte maturation and ovulation, embryo quality and implantation, placentation and the female reproductive lifespan 24 . PUFAs are also involved in immunity and the regulation of endometrial decidualization 25 . Reports have shown that PUFAs have immunomodulatory and anti‐inflammatory effects and have been shown to activate IL‐4‐driven Th2 cells and to directly inhibit the IL‐2‐induced activation of Th1 cells 26 .…”
Section: Discussionmentioning
confidence: 99%